Investigating the relationship between land use and water quality in urban water bodies - Omur Faruq; Md. Abdul Malak; Nahrin Jannat Hossain; Md. Shamsudduha Sami; Abdul Majed Sajib (Cleaner Water)
Rapid urbanization and industrialization have significantly affected global water safety, particularly in urban areas where land use patterns directly influence surface water quality (WQ). Understanding this complex relationship between Land Use and Land Cover (LULC), and WQ is crucial for sustainable water resources management. This study aimed to investigate the impact of LULC on WQ in 11 water bodies within Khulna City Corporation, Bangladesh. This study employed the Root Mean Squared Water Quality Index (RMS-WQI) model to rank the WQ status of these water bodies. The random forest algorithm was utilized on the Google Earth Engine platform to map LULC. Concurrently, canonical correlation analysis was utilized to assess the relationship between WQ and LULC buffering 100 m around each waterbody. The WQ in the study area was classified between ‘Fair’ and ‘Marginal’ based on WQI scores. The canonical correlation assessment showed that, within the buffer zone, water body size (loadings = −0.027592) and cropland area (loadings = - 0.007411) exhibited negative correlations with WQI, while other LULC variables showed positive associations. In contrast, TDS (loadings = −0.691221) and EC (loadings = 0.721202) emerged as the most significant contributors to the canonical relationship, highlighting their substantial influence on the overall WQI score. However, further studies are necessary to validate these findings by incorporating other crucial WQ indicators and time-series LULC assessments. The overall results demonstrated the suitability of the RMS-WQI model for evaluating WQ status in urban water bodies while acknowledging the inherent uncertainties such as ambiguity and the eclipsing problems. Despite these limitations, this study provides a valuable geospatial perspective on the WQ of urban water bodies, which can be useful for different stakeholders.